(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article considers the bioecological features of the biodiversity of the juniper forest of the National Natural Park “Kyrgyz-Ata”. The issues of conservation of natural biodiversity, the role of biodiversity of restored and artificially planted juniper forests in functional zones in the restoration of natural juniper forests and ecological features are reflected.